2019
DOI: 10.21276/ijcmr.2019.6.6.31
|View full text |Cite
|
Sign up to set email alerts
|

Study of Hemoglobinopathies at a Referral Laboratory in a Western District of West Bengal among the Antenatal Women and Premarital Men and Women: A 2 Years Study

Abstract: Introduction: Thalassemia and related hemoglobinopathies are a major preventable hematological disorder, affecting most parts of the Indian subcontinent. Prevention of these disorders lies in screening of at-risk population. This study was undertaken to assess the disease burden amongst predefined at-risk population in western districts of West Bengal. Material and methods: A total of 903 cases of antenatal mothers and premarital men and women in the age range of 18-40 years referred for Hemoglobin High Perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…This was in contrast to many other studies from this region of the country by Mohanty et al, Mandal et al and Chattopadhyay et al where in a community with high prevalence of beta thalassemia trait and HbE traits, HbE beta thalassaemia comes out as the commonest compound heterozygous thalassemia. 5,13,18 HbS beta thalassemia, a clinically significant thalassemia was detected in 0.025% (n=27) cases in the present study was much lower than by other previous study from the locality that had shown a prevalence of 0.15%. 13 As evident from Table 2, in spite of high prevalence of different traits especially beta thalassemia trait and HbE trait, the detection rate of different homozygous and compound heterozygous thalassaemias are much lower in the present study in comparison to many other previous studies.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…This was in contrast to many other studies from this region of the country by Mohanty et al, Mandal et al and Chattopadhyay et al where in a community with high prevalence of beta thalassemia trait and HbE traits, HbE beta thalassaemia comes out as the commonest compound heterozygous thalassemia. 5,13,18 HbS beta thalassemia, a clinically significant thalassemia was detected in 0.025% (n=27) cases in the present study was much lower than by other previous study from the locality that had shown a prevalence of 0.15%. 13 As evident from Table 2, in spite of high prevalence of different traits especially beta thalassemia trait and HbE trait, the detection rate of different homozygous and compound heterozygous thalassaemias are much lower in the present study in comparison to many other previous studies.…”
Section: Discussioncontrasting
confidence: 79%
“…Chattopadhyay et al from the same locality found high detection rate of Hb S (2.22%). 18 Kaur et al reported prevalence of sickle gene to be 0-18% in north eastern India and Colah RB et al reported an incidence of HbS trait of <5% in West Bengal. 19,20 But a recent study by Ray et al from Kolkata in a study in school going children from tribal populations of almost all districts of West Bengal reported HbS in only 0.4% of the study population; they postulated that the widely varying prevalence of alpha deletion (83%) and exceptionally low prevalence of HbS (0.4%) may be a consequence of epistasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation